A novel biomimetic trabecular bone metal plate for bone repair and osseointegration. (6th February 2023) - Ma, Zhijie; Liu, Baoyi; Li, Shuqiang; Wang, Xiaohu; Li, Jingyu; Yang, Jiahui; Tian, Simiao; Wu, Chengjun; Zhao, Dewei
Abstract: Fracture is one of the most common traumatic diseases in clinical practice, and metal plates have always been the first choice for fracture treatment because of their high strength. However, the bone plates have high elastic modulus and do not match the biomechanics of human bone, which adversely affects callus formation and fracture healing. Moreover, the complex microenvironment in the human body can induce corrosion of metallic materials and release toxic ions, which reduces the biocompatibility of the bone plate, and may necessitate surgical removal of the implant. In this study, tantalum (Ta) was deposited on porous silicon carbide (SiC) scaffolds by chemical vapor deposition technology to prepare a novel porous tantalum (pTa) trabecular bone metal plate. The function of the novel bone plate was evaluated by implantation in an animal fracture model. The results showed that the novel bone plate was effective in fracture fixation, without breakage. Both X-ray and microcomputed tomography analysis showed indirect healing by both pTa trabecular bone metal plates and titanium (Ti) plates; however, elastic fixation and obvious callus formation were observed after fixation with pTa trabecular bone metal plates, indicating better bone repair. Histology showed that pTa promoted the formation of new bone and integrated well with the host bone. Therefore, this novel pTa trabecular bone metal plate has good prospects for application in treating fractures. Graphical Abstract: